Brazilian Military Justice: Persecution againt Black, Poor and Slaughters Civils, in Operation of Law and Orden Guarantee in Río de Janeiro - Folena de Oliveira, Jorge Rubem (2021)
The military has had a strong influence on Brazilian political life since the proclamation of the Republic in 1889. Military Justice, which should judge exclusively military personnel in peacetime, throughout Brazil’s history has been used to condemn civilians, including for reasons of political persecution. In recent years there has been the condemnation of civilians, residents of favela communities in Rio de Janeiro, by the Military Justice as result of alleged crimes of disobedience and contempt in the course of law and order guarantee operations. The purpose of this article is to analyze the prosecution by the military justice of civilians (mostly poor, black and slum dwellers in Rio de Janeiro), in the course of law and order compliance operations, for framing the crimes of disobedience and contempt practiced against military people. The investigation took place through qualitative analysis of trials at the Superior Military Court, between the years 2011 to 2019, which resulted in condemnations for disobedience and contempt, in the course of operations for Guarantee of Law and Order used against residents of slum communities in Riode Janeiro, who rose up against the armed forces’ police action.